Magnetic impurities in simple metals - N. Stefanou; N. Papanikolaou; R. Zeller; P.H. Dederichs (Physica Scripta, 1994)
The local magnetic behaviour of impurities in simple monovalent metal hosts is studied systematically by means of ab-initio, local-spin-density-functional electronic structure calculations. Our results predict that besides the 3d and 4d impurities also the 5d and some sp impurities are magnetic in the late alkali metals and that local magnetism can exist for impurities not only on substitutional but also on interstitial sites.